"Street" Crime: A View from the Left - Platt, Anthony M. (Social justice, 2013)
The article summarizes and analyzes available information to provide a realistic bases for developing political strategy to address the scope and nature of street crime. Topics discussed include 7 felony offenses including homicide, robbery and aggravated assault to be more likely reported to the police, the distrust of the police as the primary reason for not reporting street crimes and how monopoly capitalism aggravated the incidence of street crimes.